A Study of Strategies for Translating Chinese Onomatopoeia Reduplication into Thai: A Case Study of The Garlic Ballads - Kaweewut, Nuttapong; Petcharatip, Kewalee (Lawarath Social E-Journal, 2024)
This article aimed to examine the translation method to translate the repeating onomatopoeia using the novel “The Garlic Ballads” (天堂蒜薹之歌) as the case study, as well as Chinese-Thai translation theories, and the word repeating methods in Thai and Chinese languages as the research scope. The research found that 93 Chinese onomatopoeias appeared in the novel, divided into four types: AA, AABB, ABAB, and ABB. They were usually placed in front of the auxiliary structural words “地” and “的” as adverbs or adjectives. The word placement does not affect the translation, but the context of the sentence is considered a major factor in translation. Therefore, the repeating onomatopoeia could be translated in two ways: maintaining of the onomatopoeic form using the Thai repeated symbols, and repeating the front and back consonants with different vowels. Regarding the number of translated syllables, there were three types: the same number of syllables as the original text; fewer syllables than the original text, and more syllables than the original text. The second method does not intend to keep the onomatopoeic form, which is used when comparable onomatopoeia cannot be found. Also, there were two ways for translating: replacement with other words, and replacement with descriptive terms, that was a description. Furthermore, the first method was found to be the most commonly used due to the similarity between Thai and Chinese languages in terms of repeating words. This method helps preserve the language usage and original meaning of the source text to a greater extent.